Bioactive compounds and aroma from the flesh of salak(Salacca zalacca) fruit and antidiabetic potential - Rahman, Md. Mokhlesur; Raja Hussin, Tengku Mohammad Ariff; Abdul Latif, Ahmad Zubaidi; Md Aris, Mohd Aznan; Awang, Mohamed; Mat So'ad, Siti Zaiton; Sanaullah Khan, Rao; Hilmi, Nur Nadhirah; Wan Nik, Wan Norsani (2018)
The development of the alpha-glucosidase inhibitor provides a new approach in the management of diabetes. α-Glucosidase enzyme belongs to the glycosidase family enzymes, cleave the glycosidic bond of the oligosaccharides that liberate glucose and its inhibition retards the carbohydrate digestion. In the present study, interest is focused on experimental researches conducted on hypoglycemic fruit particularly those which show alpha glucosidase inhibitor activity alongside bioactive components. We will studied the structural features of different of a small molecules (α-glucosidase) inhibitors are responsible for the inhibitory activities. The reported computational studies pharmacophore modelling and docking (with analogs enzymes), revealed that the topological, electronic and hydrophobicity properties determine the interactions of those molecules. The aromatic substituents connected with flexible bonds in the molecules have significant effect on the interactions, which may due to the presence of aromatic amino acid residues in the active site. Multiple sequence alignments of the α-glucosidase enzymes described that the amino acid residues are present in the active site of all the studied enzymes. This research will be concluded that this α-glucosidase inhibitor obtain from natural product (Flesh of Salacca Zalacca Fruit) used Super Critical Flud Extraction (SFE) Method are used for the treatment of diabetic type 2. The structural analysis of these synthesized and natural derivatives guide for the development of novel α-glucosidase inhibitors with free of toxicities. An efficient and selective method is needed to be established to harvest only the desirable aroma compounds and α–Glucosidase Inhibitor from the flesh of Salak fruit.